Experimental Transmission of AA Amyloidosis by Injecting the AA Amyloid Protein Into Interleukin-1 Receptor Antagonist Knockout (IL-1raKO) Mice. (May 2015) - Watanabe, K.; Uchida, K.; Chambers, J. K.; Tei, M.; Shoji, A.; Ushio, N.; Nakayama, H.
The incidence of AA amyloidosis is high in humans with rheumatoid arthritis and several animal species, including cats and cattle with prolonged inflammation. AA amyloidosis can be experimentally induced in mice using severe inflammatory stimuli and a coinjection of AA amyloid; however, difficulties have been associated with transmitting AA amyloidosis to a different animal species, and this has been attributed to the "species barrier." The interleukin-1 receptor antagonist knockout (IL-1raKO) mouse, a rodent model of human rheumatoid arthritis, has been used in the transmission of AA amyloid. When IL-1raKO and BALB/c mice were intraperitoneally injected with mouse AA amyloid together with a subcutaneous pretreatment of 2% AgNO3, all mice from both strains that were injected with crude or purified murine AA amyloid developed AA amyloidosis. However, the amyloid index, which was determined by the intensity of AA amyloid deposition, was significantly higher in IL-1raKO mice than in BALB/c mice. When IL-1raKO and BALB/c mice were injected with crude or purified bovine AA amyloid together with the pretreatment, 83% (5/6 cases) and 38% (3/8 cases) of IL-1raKO mice and 17% (1/6 cases) and 0% (0/6 cases) of BALB/c mice, respectively, developed AA amyloidosis. Similarly, when IL-1raKO and BALB/c mice were injected with crude or purified feline AA amyloid, 33% (2/6 cases) and 88% (7/8 cases) of IL-1raKO mice and 0% (0/6 cases) and 29% (2/6 cases) of BALB/c mice, respectively, developed AA amyloidosis. These results indicated that IL-1raKO mice are a useful animal model for investigating AA amyloidogenesis.